Sex as a Biological Variable in Preclinical Modeling of Blast-Related Traumatic Brain Injury - McCabe, Joseph T.; Tucker, Laura B. (Frontiers in Neurology, 2020)
Approaches to furthering our understanding of the bioeffects, behavioral changes, and treatment options following exposure to blast are a worldwide priority. Of particular need is a more concerted effort to employ animal models to determine possible sex differences, which have been reported in the clinical literature. In this review, clinical and preclinical reports concerning blast injury effects are summarized in relation to sex as a biological variable (SABV). The review outlines approaches that explore the pertinent role of sex chromosomes and gonadal steroids for delineating sex as a biological independent variable. Next, underlying biological factors that need exploration for blast effects in light of SABV are outlined, including pituitary, autonomic, vascular, and inflammation factors that all have evidence as having important SABV relevance. A major second consideration for the study of SABV and preclinical blast effects is the notable lack of consistent model design—a wide range of devices have been employed with questionable relevance to real-life scenarios—as well as poor standardization for reporting of blast parameters. Hence, the review also provides current views regarding optimal design of shock tubes for approaching the problem of primary blast effects and sex differences and outlines a plan for the regularization of reporting. Standardization and clear description of blast parameters will provide greater comparability across models, as well as unify consensus for important sex difference bioeffects.